An updated bibliography and database on forest ecosystem service valuation studies in Austria, Germany and Switzerland - Peter Elsasser; Jürgen Meyerhoff; Priska Weller (Johann Heinrich von Thünen-Institut, 2016)
This collection presents an updated bibliography of those empirical forest ecosystem service valuation studies in the German speaking countries which relate to demand oriented measures of the utility of public goods. The associated database (which is provided as a separately downloadable Excel-file) contains 77 data sets by October 2016. These data sets are characterised by about 40 descriptors (the exact number depending on the specific valuation method used in the respective study) which present details of the valuation object, the statistical and economic methods applied, the results of the valuation exercise, some other descriptors for study quality, and the associated publications. The structure of the database is explained in detail here. – – Dieser Arbeitsbericht enthält eine aktualisierte Bibliographie derjenigen empirischen Bewertungsstudien über forstliche Umweltleistungen im deutschsprachigen Raum, die nachfrageorientierte Methoden zur Bestimmung des monetären Nutzens öffentlicher Güter verwendet haben. Die damit verbundene Datenbank (die als separate Excel-Datei bereitgestellt wird) enthält derzeit (Oktober 2016) 77 Datensätze. Diese Datensätze werden - abhängig von der jeweiligen Bewertungsmethode - durch je etwa 40 Deskriptoren beschrieben, welche Einzelheiten zum Bewertungsobjekt, zu den verwendeten statistischen und ökonomischen Methoden, zu den Bewertungsergebnissen, zu einigen Qualitätsmerkmalen der Studien sowie zu den zugehörigen Publikationen enthalten. Die Struktur dieser Datenbank wird im Folgenden detailliert beschrieben.
urn:nbn:de:gbv:253-201611-dn057555-4
Keywords: 630; forest; non-market valuation; ecosystem services; Austria; Germany; Switzerland; meta-database; bibliography; Wald; Umweltbewertung; Monetarisierung; Ökosystemleistungen; Österreich; Schweiz; Deutschland; Metadatenbank; Bibliografie